Developing Literacy: Poetry: Year 3: Reading and Writing Activities for the Literacy Hour - Ray Barker, Christine Moorcroft (London : A & C Black, 2003)
A series of seven photocopiable activity books providing practical help for teachers and parents in improving children's literacy skills. Each book focuses on helping children read, write and perform poetry and the series covers the entire range of poems outlined in the Framework for Teaching.".